Enhanced magnetic coercivity and maximum energy product in double‐perovskite Y2CoMnO6single crystals. Issue 11 (8th October 2015) - Choi, H. Y.; Oh, S. H.; Moon, J. Y.; Kim, M. K.; Oh, D. G.; Lee, N.; Choi, Y. J.
Abstract : We have investigated the influence of different annealing conditions on the magnetic properties on the single crystals of double‐perovskite Y2 CoMnO6 . The ferromagnetic moment along the c ‐axis with the large magnetic coercivity and high squareness ratio was observed. Particularly, in the quenched specimen, the magnetic functionality has been greatly improved compared to that of the as‐grown crystal. The magnetic coercivity and maximum energy product have been increased by ∼120% and ∼50%, respectively, by comprising substantial disorders and defects. Our result renders an efficient route to improve the magnetic functionality in mixed‐valent magnets. (© 2015 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim) Abstract : In their newly‐grown single crystals of Y2 CoMnO6, the authors have investigated the influence of different annealing conditions on the magnetic properties. In particular, they observed the enormous enhancement of magnetic coercivity as well as maximum energy product in the quenched specimen, providing a practical technique to promote the magnetic functionality in this compound.